Pengaruh Durasi Fermentasi dan Jumlah Ragi Terhadap Kualitas Tempe Biji Nangka: Pengaruh Durasi Fermentasi dan Jumlah Ragi Terhadap Kualitas Tempe Biji Nangka - Anggi Irna; Devi Marlena; Doti Ariyani; Putri Marfhadella; Rara Saputri; Saurin Alfajari; Nurlia Latipah (ISEJ : Indonesian Science Education Journal, 2020)
Tempeh is a processed product from soybean plants. However, lately the existing soybean supply has not been able to meet the needs of the raw material for the tempe processing industry, so an alternative soy substitute is needed. One ingredient that can be used as a substitute for soybean is jackfruit seeds. This study aims to determine how to process jackfruit seeds into tempeh and comparison of nutritional content between jackfruit seed tempeh and soybean tempeh. This research was conducted by giving tempeh yeast (Rhizopusoligosporus) 0.5 gram with 500 gram jackfruit seeds. Tempe is made with a variation of fermentation time that is 36 hours, 48 ​​hours, 60 hours, and 72 hours and analyzed its nutrients namely protein, fat, carbohydrate, water and ash together with organoleptic tests of texture, color, taste and aroma of tempe. The results showed that the highest protein content, ash content and fat content obtained was 48 hours fermentation time, namely 6.85%, 1.67% and 0.73%. Meanwhile, the highest carbohydrate content obtained is 36 hours fermentation time. Water content that is in line with SNI tempeh standards is 36 hours and 48 hours, i.e. 64.8% and 65.58%. The most delicious tempeh, the most fragrant tempe and the most crispy tempeh obtained is 48 hours fermentation time.